Differences in perceived chromatic aberration between emmetropic and myopic eyes using adaptive optics - Rodriguez-Lopez, Victor; Dotor-Goytia, Paulina; Moreno, Elena; Vinas-Pena, Maria (Frontiers in Medicine, 2025)
IntroductionThe study of polychromatic visual perception is challenging due to the number of entangled factors involved in the process, from the cues within visual information from the outside world, to the ocular optics, the retinal properties, and neural adaptation processes in the brain.MethodsIn this study, we used an adaptive optics (AO)- based polychromatic visual simulator to investigate the perception of combined optical cues and its dependence on refractive error. Subjective best focus was obtained as the average of 3 repeated measurements for (1) polychromatic and five monochromatic wavelengths in the visible (450–670 nm); (2) three different visual stimuli (conventional binary sunburst, natural outdoor image, natural indoor image); and (3) under natural aberrations (no-AO) and corrected aberrations (AO) conditions. Repeatability was determined as the standard deviation across repetitions. Chromatic difference of focus (CDF) was calculated for Green-Blue (G-Blue, 550–470 nm) and Green-Red (G-Red, 550–700 nm). Longitudinal chromatic aberration (LCA) was estimated using a polynomial regression fit of the best subjective focus curves as a function of the wavelength. Nine young adults (28 ± 6 years) with different refractive profiles (6 myopic and 3 emmetropic) participated in this study.ResultsCDF showed different trends in the G-Red and the G-Blue regions, especially for the binary stimulus and after AO-correction of aberrations. However, in the myopic group, CDF was similar in absolute value for G-Blue and G-Red (0.61 ± 0.34 and 0.73 ± 0.58, respectively, p > 0.05 Mann-Whitney U test), whereas, in the emmetropic group, the chromatic difference was greater for G-Blue than for G-Red (0.58 ± 0.32 D and 0.22 ± 0.38 D, respectively, p < 0.05 Mann-Whitney U test). There was no effect of correcting natural aberrations. LCA does not vary with refractive error.DiscussionOverall, the results of this study suggest that the refractive profile may influence how visual information with specific chromatic properties is perceived and processed, potentially shaping visual mechanisms involved in chromatic defocus perception.